1998
DOI: 10.1080/09540129850123948
|View full text |Cite
|
Sign up to set email alerts
|

The validation of statements by IDUs based on the analysis of blood traces on their used syringes

Abstract: The objective of this study was to study the correlation between statements made by injecting drug users (IDUs) and the analytical observation of their used syringes, with regard to needle and syringe non-sharing and HIV serology. A survey was carried out on 137 IDUs participating in different needle exchange programmes (NEPs) throughout the Basque Autonomous Community (BAC). The used syringe they handed over in exchange for a new one was kept to study the 'DNA fingerprint' and the presence of HIV. The DNA fin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2000
2000
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…Contradictory findings in different studies could be attributed to selection bias, meaning the selection of people who were more likely to engage in high-risk injection behaviors than others regardless of participating in these programs (20,37). Few studies have shown that this program has no significant effect on high-risk injection-related behaviors (38).…”
Section: Discussionmentioning
confidence: 99%
“…Contradictory findings in different studies could be attributed to selection bias, meaning the selection of people who were more likely to engage in high-risk injection behaviors than others regardless of participating in these programs (20,37). Few studies have shown that this program has no significant effect on high-risk injection-related behaviors (38).…”
Section: Discussionmentioning
confidence: 99%
“…However, the evidence is that drug users are sufficiently reliable and able to provide descriptions of drug use, drug-related problems, their history of drug use, criminality and HIV-risk behaviours (Darke, 1998). There is a high correlation between self-reports of syringe sharing and DNA analysis of the contents of used syringes, and between selfreport of HIV status and antibody tests carried out on used syringes (Menoyo et al, 1998). An Australian study found that IDUs were motivated to participate in studies because of economic gain, an expression of citizenship, altruism, personal satisfaction, drug user activism or as part of seeking information or assistance (Fry & Dwyer, 2001).…”
Section: Hiv Risk Behavioursmentioning
confidence: 99%
“…However, self-report data are prone to bias. Despite evidence that sociodemographic and behavioral information provided by IDUs is quite reliable (Darke, 1998;Menoyo et al, 1998), several studies comparing traditional self-report to audio computer-assisted self-interview have shown that IDUs tend to under-report needle-sharing behaviors (Des Jarlais et al, 1999;Metzger et al, 2000) and to over-report protective behaviors such as condom use (Macalino et al, 2002) on interviewer-administered questionnaires.…”
Section: Introductionmentioning
confidence: 99%